MOTIVASI BELAJAR BAHASA JEPANG MAHASISWA TAHUN MASUK 2018 PRODI PENDIDIKAN BAHASA JEPANG UNP - Riska Desli Ningsih; Meira Anggia Putri (Universitas Negeri Padang, 2021)
This study aims to determine the motivation to learn Japanese in the 2018 students in Japanese Language Education Study Program at UNP. The method used in this study is a quantitative method and this type of research is descriptive. The population of this study was to 63 students. The sampling technique is total sampling technique, as many as the 2018 students in Japanese language education study program at Universitas Negeri Padang. The data collection technique used is a questionnaire with a Likert scale. The data analysis technique used is descriptive with a percentage.The results of this study are the average questionnaire of the motivation to learn Japanese for the 2018 Students in Japanese Language Education Study Program at UNP. The Motivation to learn Japanese students in 2018 students in Japanese Language Education Study Program at UNP has an average score of 70.6% which is category in classified as